Smooth operation: with Apple's new Macs, performance justifies cost. - Bickers, Charles (Far Eastern Economic Review, 1998)
With Apple Computer's most recent operating system, Mac OS8, performance justifies the price. The main argument against purchasing Apple products is simply that they are not Windows PCs and that they accordingly lack the extensive range of software and hardware created for the latter. This is hardly a significant difficulty: Software and hardware for Macs are available for every operation that the user could want.